Implementing Collaborative Writing in Chinese EFL Classrooms: Voices From Tertiary Teachers - Zheng, Yao; Yu, Shulin; Lee, Icy (Frontiers in Psychology, 2021)
While collaborative writing has been increasingly investigated in educational research, little is known about whether and how it is adopted as a pedagogical activity in classroom contexts. This exploratory study investigated EFL teachers' perceptions of the implementation of collaborative writing in Chinese tertiary institutions. The analysis of the in-depth interviews with 31 EFL teachers from 13 institutions in the People's Republic of China and their teaching materials reveals mismatches between their perceptions and practices, as well as their perceptions and knowledge. While the teachers perceived collaborative writing as valuable and feasible, more than half of them were not using it, and their perceptions were not supported by sound teacher knowledge. Practical implications are provided for implementing collaborative writing in classroom contexts.